WAYS TO COMPLETE PRACTICAL ASSIGNMENTS IN THE TEXTBOOK OF NATIVE LANGUAGE AND READING LITERACY - Nazarova Kamuna Farhad daughter (Scholar Express Journal, 2023)
Through innovative technologies, aspects of the formation of knowledge about science in students are analyzed. By applying the chosen method, students ' interest in history, national values increases. Readers approach the topic creatively, try to freely express their opinion. With this, their independent opinion is terraced, the world view grows, their interest in the lesson increases, their resourcefulness, ingenuity, speed, activity increases.
Keywords: pedagogical categories; method; innovative technologies